UTANG PIUTANG DALAM PERSPEKTIF FIQIH - Sonafist, Y. (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2015)
The economic crisis is often the case that have an impact on the global financial crisis and resulting financial conditions of individuals and families experiencing instability. Many have suddenly become poor or otherwise many who suddenly become rich. The next result is empirically many people who sell loans or receivables to others with cash because of being pressured by the needs that must be met. Buying and selling in this form in terms fiqhiyyah is called Baiuddain; for example, person A owes the B. Agreement is corroborated by accounts payable certificate. Due to the urgent need, certificate of accounts payable were sold B to person C, and based on the certificate, the C collect the debt on the A. Or the A book or asked for an item (say furnishings) on the B and has been partially paid the price (perskot), then after that if A is in need of money and need cash, so he sold the debt on the C with a slight advantage. So, how is the law of sale and purchase of loans or receivables (Bai al-dain) is in the perspective of Islamic perspective? seems the scholars have different opinions about this. More can be read in the following text.Â Krisis perekonomian yang sering terjadi kadang-kadang membawa dampak pada krisis keuangan global dan mengakibatkan kondisi keuangan perorangan dan keluarga mengalami ketidak-stabilan. Banyak yang mendadak menjadi miskin atau sebaliknya banyak yang mendadak menjadi kaya. Akibat selanjutnya secara empirik banyak, orang yang menjual hutang atau piutangnya kepada orang lain dengan uang cash karena terdesak oleh kebutuhan yang harus segera dipenuhi. Jual beli dalam bentuk ini dalam istilah fiqhiyyah disebut Baiâuddain; misalnya si A berutang pada si B. Perjanjian hutang piutang dikuatkan dalam akte perjanjian hutang piutang. Karena kebutuhan yang mendesak, akte perjanjian hutang piutang tersebut dijual B kepada si C, dan berdasarkan akte tersebut, si C menagih hutang pada si A.Atau si Amemesan atau minta dibuatkan suatu barang (katakanlah perabot) pada si B dan telah dibayar sebagian harga (perskot), lalu setelah itu si A mengalami kesulitan ekonomi dan butuh uang cash, maka ia menjual utangnya itu pada si C dengan sedikit keuntungan. Lantas, bagaimanakah hukum jual beli hutang atau piutang (Baiâ al-dain) ini dalam perspektif Fiqh Islam? nampaknya para ulama berbeda pendapat tentang hal ini. Selengkapnya dapat dibaca dalam tulisan berikut.